Shaped By the Environment: The Influence of Childhood Trauma Exposure, Individual Socioeconomic Position, and Neighborhood Disadvantage on Brain Morphology - (:unkn) unknown (My University, 2020)
The relationship between an individual’s socioeconomic position (SEP) and their overall physical and mental health has been well demonstrated. Far less is known about how area-level factors, such as neighborhood disadvantage, “get under the skin”. Previous research indicates lower SEP and childhood trauma negatively effects brain structure and function. The hippocampus, amygdala, and ventromedial prefrontal cortex (vmPFC) are particularly vulnerable to adversity. The current study investigated how individual SEP, childhood trauma, and neighborhood disadvantage impact these structures. Two-hundred and fifteen individuals were recruited from an Emergency Department in southeastern Wisconsin. Two-weeks post-traumatic injury, participants completed a structural magnetic resonance imaging scan and various self-report measures. Area Deprivation Index (ADI), a measure of a neighborhood’s socioeconomic disadvantage, and neighborhood homicide rates were derived from participants’ addresses. Results of hierarchical multiple linear regression analyses revealed ADI was associated with hippocampal volume, over and above individual variables while vmPFC was significantly impacted by individual income but not neighborhood disadvantage. Interestingly, amygdala volume was only related to gender. In an exploratory analysis, we used Structural Equation Modeling to investigate how a model with individual and neighborhood factors would interdependently relate to brain structure. Neighborhood variables were significantly correlated with Individual SEP measures. Similar to the regression analysis, we demonstrated that vmPFC volume is significantly associated with individual SEP but not neighborhood factors. This study provides additional support that neuroscience has an imperative role in identifying and addressing health disparities and help fuel the development of interventions targeting at-risk populations.
Keywords: Amygdala; Hippocampus; Neighborhood Disadvantage; Prefrontal Cortex; Socioeconomic Position; Structural Imaging